Acute fulminant myoglobinuric polymyositis with picornavirus-like crystals. Issue 8 (August 1977) - Fukuyama, Y; Ando, T; Yokota, J
Abstract : Myoglobinuria was found in an 11 month old girl suffering from fever, dyspnoea, and muscle hypotonia. Muscle biopsy showed focal degenerative necrosis of the muscle fibres. Electronmicroscopically, picornavirus-like crystals were demonstrated in the muscle fibres. These and other findings strongly suggest that she suffered from acute myositis with myoglobinuria probably caused by Coxsackie B6 virus infection. The causal relationship of viral infection (Coxsackie, influenza, or myxo-viruses) and acute or chronic polymyositis with or without myoglobinuria is discussed.